Survival and risk of death among women with reports of intimate partner violence during pregnancy: a national cohort study in Brazil - Marcela Quaresma Soares; Cristiane Magalhães de Melo; Eduardo Fernandes e Silva; Isabella Vitral Pinto; Paula Dias Bevilacqua (BMC Public Health)
Abstract Purpose This study aimed to analyze the factors associated with the risk of death and survival probability among women who experienced intimate partner violence (IPV) during pregnancy. Methods This retrospective cohort study used national data from Brazil. Survival probability was estimated using the Kaplan–Meier method, while the Cox proportional hazards model was applied to investigate risk factors associated with death. Results Significant risk factors identified included older age (HR = 1.03 [1.01–1.07]), disability or disorder (HR = 2.40 [1.22–4.74]), aggression involving firearms (HR = 13.15 [2.64–65.47]) or sharp objects (HR = 10.59 [2.19–51.12]), and having more than one report of violence (HR = 1.78 [1.13–2.82]). Being in the second trimester of pregnancy was associated with a lower risk of death compared to the first trimester (HR = 0.49 [0.30–0.81]). Femicide was the leading cause of death, accounting 45.7% of all deaths. Conclusion IPV during pregnancy significantly increases the risk of death, emphasizing the importance of systematic screening during prenatal care. Despite being a major cause of death, femicide remains underreported in maternal mortality statistics. The findings underscore the urgency of improving health surveillance systems to ensure better detection, recording, and prevention of fatal outcomes among women exposed to IPV.